'No test, no disease': Multilevel barriers to HIV testing among young men who have sex with men and transgender women in three semi-urban areas in Thailand. Issue 9 (3rd August 2022) - Fongkaew, Kangwan; de Lind van Wijngaarden, Jan W.; Tepjan, Suchon; Chonwanarat, Nuttapon; Akkakanjanasupar, Pakorn; Newman, Peter A.
Abstract: Young gay and other men who have sex with men and young transgender women in Thailand continue to be at high risk for HIV infection. We explored multilevel influences on HIV testing in order to inform the design of tailored interventions. We conducted four focus group discussions with 16–20-year-old gay men and transgender persons ( n = 25) and 17 key informant interviews with healthcare providers, NGO leaders, and youth advocates. Focus groups and interviews were transcribed and reviewed using thematic analysis in Thai and English language by a bilingual team. We identified intersecting, culturally situated barriers at individual (lack of HIV knowledge, low HIV risk perception, denial), social (intersectional sexual- and HIV-related stigma, lack of family communication), institutional (inadequate and non-LGBT-inclusive sexual health education in schools, lack of youth-friendly clinics) and policy levels (parental consent requirements for HIV testing by minors). Multilevel and multisystem factors coalesce to form extensive barriers to HIV testing access and utilisation and promote disengagement from HIV prevention more broadly. Multicomponent, youth-engaged interventions informed by Thai sociocultural history and practices are needed in renewed approaches to HIV prevention and testing to end the epidemic among young gay and transgender people in Thailand.